MENGKOMUNIKASIKAN SECARA KREATIF KEBIJAKAN DAN LAYANAN PERPUSTAKAAN MELALUI MEDIA SOSIAL - Isrowiyanti Isrowiyanti (Jurnal Pustaka Ilmiah, 2018)
Libraries as nonprofit institutions are required to continue to develop their serviceseven though sometimes they have to face very limited budget conditions. The existingfacilities and opportunities must be optimized so that the library program continues andreaches as many users as possible. Information technology and telecommunicationsare both opportunities and challenges for librarians in order to enforce the existenceof libraries amid the shifting patterns and lifestyles of librarians in addition to thelimitations possessed by libraries. This paper describes how library efforts utilize thetrend of virtual communication to communicate creatively library policies throughsocial media.